2012
DOI: 10.1117/1.jbo.17.6.066009
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo photometric and polarimetric multilayer characterization of human healthy colon by multispectral Mueller imaging

Abstract: Healthy human colon samples were analyzed ex vivo with a multispectral imaging Mueller polarimeter operating from 500 to 700 nm in a backscattering configuration with diffuse light illumination impinging on the innermost tissue layer, the mucosa. The intensity and polarimetric responses were taken on whole tissues first and after progressive exfoliation of the outer layers afterwards. Moreover, these measurements were carried out with two different substrates (one bright and the other dark) successively placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…However, the tissue examined in this paper was, by comparison, structurally homogenous and isotropic. This is supported by previous work by our group and others [8,19], which has shown that depolarisation dominates over retardance and diattenuation, making it unlikely that additional contrast would be seen by rotating the incident polarisation angle. Indeed, Mueller polarimetric analysis of bowel tissue has shown it to be a partial depolariser with insignificant diattenuation and retardance [20].…”
Section: Discussionsupporting
confidence: 71%
“…However, the tissue examined in this paper was, by comparison, structurally homogenous and isotropic. This is supported by previous work by our group and others [8,19], which has shown that depolarisation dominates over retardance and diattenuation, making it unlikely that additional contrast would be seen by rotating the incident polarisation angle. Indeed, Mueller polarimetric analysis of bowel tissue has shown it to be a partial depolariser with insignificant diattenuation and retardance [20].…”
Section: Discussionsupporting
confidence: 71%
“…It was demonstrated that early stage cancerous human colon is less depolarizing than healthy colon through ex vivo measurements with a multispectral Mueller polarimetric imaging system [14]. Using the same system, it was also shown that tissue depolarization could provide useful image contrast to quickly identify the stage of colon cancer development [16], and the relevant histopathological reasons were discussed in terms of tissue layers [17] and tissue absorption and scattering [15]. The system was also found to be a promising tool to evaluate colon cancer progression and residual cancerous tissue after radio-chemical therapy [20].…”
Section: The Biomedical Applications Of Mueller-polarimetric Imagingmentioning
confidence: 99%
“…The characteristic polarization information of interest is carried by a 4 3 4 matrix named a Mueller matrix and this can be experimentally obtained from Mueller polarimetry and polarimetric imaging. In recent years, an increasing number of biomedical applications of Mueller polarimetric imaging techniques have been proposed [5], e. g. oral cancerous legion detection [13], cervical cancer and colon cancer detection and staging [12,[14][15][16][17][18][19], assessment of cancer therapy [20], partial bladder obstruction diagnosis [21], guiding mass spectrometry for instant pathology [22], characterizing collagen fibres [23], and these have demonstrated advantages over polarization blind imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from polarization, spectral features of the scattered light also carry information on the microstructure of biological samples, therefore can be applied in diagnosis of cancerous tissues [19]. Studies have shown that combining polarization and spectral techniques can provide more powerful tools for cancer diagnosis [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%